Ethnobotany of Merpayang (Scaphium macropodum Miq.) Beumee K. Heyne as a Medicinal Plant on The Pengulu Ethnic Sarolangun Jambi - Rizky Febriana Lubis; Agus Hikmat; Ervizal A. M. Zuhud (Media Konservasi, 2019)
Merpayang fruit (Scaphium macropodum Miq.) Beumee Ex K Heyne has long been known to have medicinal properties, one of them the Pengulu ethnic. The research aimed was to analyze the ethnobotany of merpayang utilization in the Pengulu ethnic community of Jambi. The method used in this study was qualitative. Data collection used direct interviews with informants of Pengulu ethnic community with  selected by snowball sampling. Data analysis was carried out by cross checking, summarizing, synthesizing, and narrating with descriptive analysis and evaluation. The results of study showed that the Pengulu ethnic uses merpayang for traditional medicines, including heartburn, fever, laxative, hemorrhoid/Ambien, coughing, and itching. In addition to the fruit, the Pengulu ethnic uses other parts of merpayang plant, such as sap, tree skin, roots as medicines. Keywords: ethnobotany, medicinal plant, merpayang, Sarolangun